Improving sport science impact in athlete-led practice environments: a track cycling persepctive - Stadnyk, A.; Impellizzeri, F.; Stanley, J.; Menaspà, P.; Slattery, K. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Like most high performance sports, track cyclists are typically supported within the training environment by coaches and interdisciplinary practitioners who, using evidence-based practices, guide the athlete through the process of performance development. To effectively impact their practices and athlete performance, practitioners must be able to implement their knowledge and expertise in a way that complements the wider performance team. The aim of this study was to examine track cycling coaches` perspectives of the role and impact of sport science and research on their practice and the athlete development process. METHODS: Semi-structured interviews were conducted with elite track cycling coaches (n=8) who had been working at the highest level of the sport (Olympics, UCI World Championships). The interviews addressed factors contributing to athlete preparation, and the current and potential impact of sport science on the development of elite track cyclists. Reflexive thematic analysis was conducted to identify common themes in participants` experiences and perspectives. RESULTS: Three principal themes were identified from the data: `conversation & the information dynamic`, highlighting the impact of information and feedback within the performance team for developing collective training intelligence; `integrating performance components for the individual`, detailing the importance of individualised and integrated approaches to athletes` performance needs; and, `science to complement the vision`, examining the value of filtered data, and limitations of research in practice. CONCLUSION: The findings highlighted two key contributors to performance team effectiveness: athletes deeply invested in, and actively contributing to, the development process; and, performance staff identifying and filtering research and data to impact decision making and athlete development. A four-stage model was developed from the collective findings for guiding sport scientists` impact in athlete-led practice environments. Additionally, the model outlines sport scientist-supportive actions for coaches and athletes, along with practice-supportive actions for researchers, to improve impact within the sport.